THE EFFECT OF OXYTOCIN MASSAGE AND AROMATHERAPY ON REDUCING ANXIETY AMONG PRIMIPARA POSTPARTUM - Denis Mulanita Pratiwi; Achmad Zulfa Juniarto; Sri Rejeki (Jurnal Ilmu Keperawatan Maternitas, 2023)
Post partum is a critical period, especially for primiparous mothers. Mothers are faced with various changes, both physically and psychologically and in their social life. In the post partum phase, the mother will experience fatigue, changing roles, changing moods such as feelings of sadness and anxiety. Most postpartum mothers feel very anxious in adapting to their post-partum life. Previous research has shown that oxytocin massage can increase milk production and make mothers relax so that the feeling of tension is reduced. Aromatherapy also affects the level of anxiety of post partum mothers in milk production. This study aims to determine the effect of oxytocin massage and aromatherapy on reducing anxiety in primiparous postpartum mothers. This study uses a quasi-experimental design in the form of a pre-posttest design with a control group. The population of this study were all primiparous post partum patients who were in the inpatient room. The sampling technique used in this research is purposive sampling. The sample in this study were primiparous post partum patients on the first day (24 hours post partum), totaling 60 respondents, consisting of 30 respondents in the control group and 30 respondents in the intervention group. Based on statistical tests using the Wilcoxon test, the results were p = 0.000 <0.05, namely there was a difference in anxiety in primiparous postpartum mothers in the intervention group before and after being given the oxytocin massage and aromatherapy intervention. given the intervention (p = 0.000 < 0.05) with the mean rank of the intervention group (24.17) smaller than the mean rank of the control group (36.83) and there was a difference between the intervention group and the control group (p = 0.000 < 0 0.05) with the mean rank of the intervention group (39.43) greater than the mean rank of the control group (15.57). The conclusion obtained is that oxytocin massage and aromatherapy are effective in reducing anxiety in primiparous postpartum mothers. Key words : anxiety, oxytocin massage, aromatherapy, post partum, primipara